2021
DOI: 10.1177/17562872211007978
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography as a new, non-invasive diagnostic modality for the diagnosis of penile elasticity: a prospective multicenter study

Abstract: Objective: Shear wave elastosonography (SWE) could be used to evaluate the elasticity of penile tissue. Few studies in the literature, however, have investigated its use in patients with erectile dysfunction (ED) or have attempted to correlate findings with International Index of Erectile Function (IIEF-5) scores. The primary aim of this study was to evaluate the characteristics of erectile tissue using SWE and to determine possible relationships with IIEF-5 and Erection Hardness Scale (EHS) scores. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…SWE is an operator-independent method that can be easily reproduced [15,16]. Moreover, it can be used to obtain a quantitative value of the analyzed tissue and to eventually compare the results obtained following the targeted treatments [17].…”
Section: Discussionmentioning
confidence: 99%
“…SWE is an operator-independent method that can be easily reproduced [15,16]. Moreover, it can be used to obtain a quantitative value of the analyzed tissue and to eventually compare the results obtained following the targeted treatments [17].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Zhang et al [ 29 ] measured penile elasticity in erectile dysfunction patients and PD patients before and after a pharmacologically induced erection. They reported that there was a significant increase in viscoelasticity in patients with pharmacologically induced erections, demonstrating that SWE could be used to measure dynamic changes in erection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Illiano et al [ 30 ] analyzed 270 patients with various degrees of erectile dysfunction and observed a correlation between the worsening of IIEF-15 score and a higher degree of penile stiffness demonstrated by the erection hardness score; they also observed a reduction in elasticity demonstrated by an increase in kPa values diagnosed by SWE.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the rate of the patients with psychogenic ED in the ED group was unclear, and this may have affected the research findings. On the contrary, Illiano et al determined that SWE was negatively correlated with IIEF-5 and erection hardness score [ 25 ]. The findings of our study are consistent with the study of Illiano et al…”
Section: Discussionmentioning
confidence: 99%